The peculiarities of reduction of iron (III) oxides deposited on expanded graphite. Issue 2 (23rd January 2014) - Lutfullin, Marat; Shornikova, Olga; Dunaev, Alexander; Filimonov, Dmitry; Schur, Alina; Saidaminov, Makhsud; Sorokina, Natalya; Avdeev, Viktor
Abstract: Abstract : A reduction of iron (III) oxides deposited on expanded graphite (EG) matrixes of three types in hydrogen flow was studied in dynamic and static regimes. In the dynamic regime, the EG matrix was shown not to influence the temperature range of the iron (III) oxide reduction. However, the C/O atomic ratios, varying depending on the type of EG matrixes, affect the completeness of reduction of these oxides to metallic iron. The reduction kinetics of iron (III) oxides deposited on EG and of bulk oxides were found to be similar and could be described by the combination of expanded Prout–Tompkins autocatalysis and n -dimensional growth of nuclei models. The prolonged hydrogen treatment at 600 °C of the samples in the static regime results in quantitative reduction of iron (III) oxide to α-Fe independent of the type of EG matrix used. The obtained samples demonstrate the relatively high values of saturation magnetization of 35 emu/g together with a high sorption capacity for crude oil of 93 g/g.